Particulate matter forecast and prediction in Curitiba using machine learning - Chaves, Marianna Gonçalves Dias; da Silva, Adriel Bilharva; Mercuri, Emílio Graciliano Ferreira; Noe, Steffen Manfred (Frontiers in Big Data, 2024)
Air quality is directly affected by pollutant emissions from vehicles, especially in large cities and metropolitan areas or when there is no compliance check for vehicles emissions standards. Particulate Matter (PM) is one of the pollutants emitted from fuel burning in internal combustion engines and remains suspended in the atmosphere, causing respiratory and cardiovascular health problems to the population. In this study, we analyzed the interaction between vehicular emissions, meteorological variables and particulate matter concentrations in the lower atmosphere, presenting methods for predicting and forecasting PM 2.5. Meteorological and vehicle flow data from the city of Curitiba, Brazil, and particulate matter concentration data from optical sensors installed in the city between 2020 and 2022 were organized in hourly and daily averages. Prediction and forecasting were based on two machine learning models: Random Forest (RF) and Long Short-Term Memory (LSTM) neural network. The baseline model for prediction was chosen as the Multiple Linear Regression (MLR) model and for forecast we used the naive estimation as baseline. RF showed that on hourly and daily prediction scales the planetary boundary layer height was the most important variable, followed by wind gust and wind velocity in hourly or daily cases, respectively. The highest PM prediction accuracy (99.37%) was found using the RF model on a daily scale. For forecasting, the highest accuracy was 99.71% using the LSTM model for one hour forecast horizon and with 5 hours of previous data used as input variables. The RF and LSTM models were able to improve prediction and forecasting compared to MLR and Naive, respectively. The LSTM was trained with data corresponding to the period of the Covid-19 pandemic (2020 and 2021) and was able to forecast the concentration of PM 2.5 in 2022, in which the data shows that there was greater circulation of vehicles and higher peaks in the concentration of PM 2.5. Our results can help the physical understanding of factors influencing pollutant dispersion from vehicles emissions at the lower atmosphere in urban environment. This study supports the formulation of new government policies to mitigate the impact of vehicle emissions in large cities.